IDENTIFYING THE BALANCE BETWEEN FINANCIAL REWARDS AND NON- FINANCIAL REWARDS TO RETAIN TALENT MEDIATED BY MOTIVATION IN MALDIVES ELECTRICITY INDUSTRY. - Aishath Faseeha Mohameda (International Journal of Educational Excellence and Innovation, 2024)
This study investigates the variables affecting the Maldives electricity industry's ability to retain talent. Talent has not yet been given a uniform definition. According to the organisation and the services they offer to customers, talents are defined. Employees who have the knowledge, skills, and performance to strategically contribute to the organization’s goals and objectives are referred to as having talents.The issues raised in this article include the gap between motivation and rewards caused by the dearth of available literature, the academic gap discovered in recognising the balance between financial rewards and non-financial rewards to retain talent in various industries, and the paucity of literature pertaining to the relationship between motivation and talent retention. The purpose of this study is to address the mentioned issues. This study is focused in the cities of Maldives Electricity industry.EFA, CR, AVE, Cronbach's Alpha, CFA, and the Sobel test were all performed during the data analysis stage. 298 samples were used in this study to analyse. This study added to the body of knowledge on talent retention and revealed fresh research directions. The findings of this study enhanced the model of talent retention. Some results were at odds with the body of knowledge, which elevated the study's stature and the body of knowledge.